A survey of the library facilities and collections of the public elementary schools in Marikina City based on the standards for Philippine libraries a follow-up study - Hizon, Patricia Felise P. (2016)
This study focuses on the compliance of the public elementary school libraries in Marikina City with the collection and facility standards of the Standards for Philippine Libraries by the Department of Education.